Análisis de proyecto de energía renovable para la parroquia San Agustín del Cantón Santa Rosa, Provincia de El Oro para potenciar el desarrollo integral del sector. - Jaramillo Simbaña, Raquel Magali (2015)
The study focused on the analysis of CDM (clean development models) (solar energy / solar panels) for clean energy (electric power) in the parish of St. on the parroquia ‘San Agustin’ to Santa Rosa Canton, to enhance the development of the sector. This study demonstrates the importance of providing renewable electricity the parroquia and in which the basic information gathered, project background, chosen alternative that will serve the supply and the proposed design of the different parts of which shall consist system parameters is included. Among the main activities of the Government, is that of meeting the basic needs of the cantons and rural populations of the provinces, primarily emphasizing those relating to the preparation of studies and designs systems for the provision of suitable renewable power infrastructure safeguarding the unmet needs of the residents.